2019
DOI: 10.1186/s12985-019-1127-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of geraniin on dengue virus type-2 infected BALB/c mice

Abstract: Background Dengue continues to be a major international public health concern. Despite that, there is no clinically approved antiviral for treatment of dengue virus (DENV) infections. In this study, geraniin extracted from the rind of Nephelium lappaceum was shown to inhibit the replication of DENV-2 in both in vitro and in vivo experiments. Methods The effect of geraniin on DENV-2 RNA synthesis in infected Vero cells was tested using quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…In immunocompetent mice (Male BALB/c mice of age 8 weeks), DENV-associated clinical symptoms were observed [32,33]. These clinical responses were consistently observed in our experimental model in mice, and crocetin treatment at a dosage of 50 mg/kg of mice improved leucopenia, thrombocytopenia and liver transaminases in DENV-infected mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In immunocompetent mice (Male BALB/c mice of age 8 weeks), DENV-associated clinical symptoms were observed [32,33]. These clinical responses were consistently observed in our experimental model in mice, and crocetin treatment at a dosage of 50 mg/kg of mice improved leucopenia, thrombocytopenia and liver transaminases in DENV-infected mice.…”
Section: Discussionsupporting
confidence: 78%
“…DENV-associated clinical indications, including leucopenia and thrombocytopenia, were explained by the previous finding that liver injury was linked with elevated transaminases [ 30 , 31 ]. In immunocompetent mice (Male BALB/c mice of age 8 weeks), DENV-associated clinical symptoms were observed [ 32 , 33 ]. These clinical responses were consistently observed in our experimental model in mice, and crocetin treatment at a dosage of 50 mg/kg of mice improved leucopenia, thrombocytopenia and liver transaminases in DENV-infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RT-PCR is usually used for validating novel DENV diagnostic tests including RDTs [ 7 ]. The assay also is used to quantify DENV RNA in laboratory and clinical samples to assess virus burden [ 8 ] and to determine the efficacy of vaccines [ 9 ] and anti-DENV drugs [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that polyphenol geraniin reduced viremia when administered to mice 72 h after infection (hpi) at a concentration of 131.30 μM prepared in 100 μL PBS. Additionally, histopathology showed that treatment with geraniin 24 h prior to infection could prevent severe liver damage caused by DENV-2 [ 47 ].…”
Section: Geraniinmentioning
confidence: 99%